The S-curvature of Finsler warped product metrics - Gabrani, Mehran; Rezaei, Bahman; Sevim, Esra Sengelen (Elsevier, 2024)
The class of warped product metrics can often be interpreted as key space models for general theory of relativity and in the theory of space-time structure. In this paper, we study one of the most important non -Riemannian quantities in Finsler geometry which is called the S -curvature. We examined the behavior of the S -curvature in the Finsler warped product metrics. We are going to prove that every Finsler warped product metric R x Rn has almost isotropic S -curvature if and only if it is a weakly Berwald metric. Moreover, we show that every Finsler warped product metric has isotropic S -curvature if and only if S -curvature vanishes. (c) 2023 Elsevier B.V. All rights reserved.
Keywords: Finsler Warped Product Manifold; S-Curvature; Weakly Berwald Manifolds